2021
DOI: 10.1111/pce.14142
|View full text |Cite
|
Sign up to set email alerts
|

Pest and disease management by red light

Abstract: Light is essential for plant life. It provides a source of energy through photosynthesis and regulates plant growth and development and other cellular processes, such as by controlling the endogenous circadian clock. Light intensity, quality, duration and timing are all important determinants of plant responses, especially to biotic stress. Red light can positively influence plant defence mechanisms against different pathogens, but the molecular mechanism behind this phenomenon is not fully understood. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 159 publications
0
26
0
Order By: Relevance
“…LEDs can also be used for pest management. Several studies showed the influence of the light environment in greenhouses (including the length of the photoperiod and light quality) (for review, see Gallé et al, 2021 ; Lazzarin et al, 2021 ), on plant resilience against pathogens such as B. cinerea in strawberries ( Meng et al, 2020 ) or tomatoes ( Yang et al, 2015 ). Understanding how supplemental light through LEDs acts on plant growth and defense may lead to novel sustainable horticultural methods for pest management.…”
Section: Conclusion and Future Research Perspectivesmentioning
confidence: 99%
“…LEDs can also be used for pest management. Several studies showed the influence of the light environment in greenhouses (including the length of the photoperiod and light quality) (for review, see Gallé et al, 2021 ; Lazzarin et al, 2021 ), on plant resilience against pathogens such as B. cinerea in strawberries ( Meng et al, 2020 ) or tomatoes ( Yang et al, 2015 ). Understanding how supplemental light through LEDs acts on plant growth and defense may lead to novel sustainable horticultural methods for pest management.…”
Section: Conclusion and Future Research Perspectivesmentioning
confidence: 99%
“…Tremendous reports demonstrated the essential roles of a certain spectrum of light in promoting plant defense against pathogen infection and herbivore infestation. Normally, red light increases plant resistance to various pathogens, herbivores, and nematodes ( Yang et al, 2018b ; Gallé et al, 2021 ), although the molecular mechanisms were still obscure. As described above, plant innate immunity is an essential strategy deployed by plants to counter invaders.…”
Section: Light Regulated Plant Innate Immunity Against Insect-borne P...mentioning
confidence: 99%
“…Among the various phytohormones, SA, jasmonic acid (JA), and ethylene (ET) are widely reported to be resistant to biotic stresses. Generally speaking, SA is usually considered as a primary hormone against biotrophic, hemibiotrophic pathogens, and phloem-feeding insects; JA and ET mainly regulate plant immune responses against chewing insects and necrotrophic pathogens ( Lazebnik et al, 2014 ; Li et al, 2019 ; Gallé et al, 2021 ). Understanding how plants coordinate phytohormone signaling to counteract serious external threats makes great sense for exploring novel disease resistance strategies.…”
Section: Light-mediated Phytohormone Signaling Against Insect-borne P...mentioning
confidence: 99%
See 2 more Smart Citations